Periprocedural myocardial infarction and injury in elective coronary stenting. (20th January 2018) - Zeitouni, Michel; Silvain, Johanne; Guedeney, Paul; Kerneis, Mathieu; Yan, Yan; Overtchouk, Pavel; Barthelemy, Olivier; Hauguel-Moreau, Marie; Choussat, Rémi; Helft, Gérard; Le Feuvre, Claude; Collet, Jean-Philippe; et al.
Abstract: Aims: To assess the incidence, risk factors and prognosis of periprocedural myocardial infarction (MI) and myocardial injury in patients undergoing elective percutaneous coronary intervention (PCI). Methods and results: We included all consecutive patients who underwent elective PCI with a negative troponin level at admission from 1 January 2014 to 31 December 2015. The primary endpoint was defined as the composite of periprocedural MI (Type 4a MI), stent thrombosis (Type 4b MI), and myocardial injury according to the Third universal definition of MI. Multivariable analysis was performed to identify independent predictors of periprocedural MI and myocardial injury and its relation to 30-day and 1-year clinical outcome. Of the 1390 elective PCI patients, the primary endpoint occurred in 28.7% of patients, including 7.0% of Type 4a MI, 0.14% of Type 4b MI, and 21.6% of myocardial injury. Independent risk factors for the occurrence of the primary endpoint were left main PCI, total stent length >30 mm, multiple stenting, chronic kidney disease (estimated glomerular filtration rate <60 mL/min) and age >75 years. At 30 days, patients with periprocedural MI and myocardial injury had a higher rate of cardiovascular events [5.5% vs. 1.2%, adjusted hazard ratio (adjHR) = 3.8, 95% confidence interval (CI) 1.9–6.9; P < 0.001] mainly driven by ischaemic events (3.2% vs. 0.6%, HR 5.9, 95% CI 2.9–20; P < 0.0001). At 1-year, the risk of ischemic events remained higher in the periprocedural MI and myocardial injury group (adjHR = 1.7, 95% CI 1.1–2.6; P = 0.004). Conclusions: Periprocedural MI and injury are frequent complications of elective PCI associated with an increased rate of cardiovascular events at 30 days and 1 year.